Glutathione S-transferase M1 and T1 null genotypes as risk factors for oral leukoplakia in ethnic Indian betel quid/tobacco chewers - Nair, Urmila; Nair, Jagadeesan; Bartsch, Helmut (Carcinogenesis, 1999)
Oral cancer is the most common cancer in males and third most common in females in India, the main causative agent being the use of chewing tobacco with or without betel quid (BQ). However, nothing is known about the role of the host metabolic genes in oral cancer in ethnic Indian population. In this study, the prevalence of GSTM1 and GSTT1 null genotypes (GSTM1*2 and GSTT1*2) in oral premalignant leukoplakia cases and controls was ascertained in genomic DNA by a multiplex PCR technique. Biopsies taken from 98 oral leukoplakia patients and exfoliated cells from 82 healthy controls both of Indian ethnicity were analysed. GSTM1*1 (active) was present in 83% and GSTT1*1 (active) was present in 78% of all control subjects, while prevalence of GSTM1*2 and GSTT1*2 null genotypes was significantly higher among oral leukoplakia cases. The prevalence of GSTM1*2 in leukoplakia cases was 81.6% compared with 17% in controls [odds ratio (OR), 22; 95% confidence interval (CI), 10-47] and GSTT1*2 was 75.5% in the cases versus 22% in controls (OR, 11; 95% CI, 5-22). Combined null genotypes of GSTM1 and GSTT1 prevailed in 60.2% of the cases with none detected in controls. Glutathione S-transferase M1 and T1 enzymes are both known to catalyse detoxification of reactive oxygen species, lipid peroxidation products and tobacco-derived carcinogens that have been found in the saliva of BQ/tobacco chewers. Our results, still requiring confirmation by a larger study, demonstrate that the null genotypes of both GSTM1 and GSTT1 increase with high penetrance, separately or in combination, the risk for developing leukoplakia in an Indian ethnic population.
Gesehen am 02.02.2021